Broadband working-waveband-tunable polarization converter based on anisotropic metasurface. (1st February 2017) - Lin, Yu; Wang, Lei; Gao, Jun; Lu, Yichao; Jiang, Suhua; Zeng, Wei
Abstract: We experimentally and theoretically demonstrate an ultrathin, broadband, and highly efficient metamaterial-based polarization converter with a metasurface/insulator/metal (MIM) configuration. In such a system, the resonance undergoes a transition from a vertical Fabry–Pérot type to a transverse type as the spacer thickness decreases. By changing the spacer thickness from 1 to 15 mm, the working waveband of this device could be tuned from 10.9–12.9 to 6–8 GHz without compromising the polarization conversion efficiency. Equivalent circuit theory and the transfer matrix method are used for demonstrating the physical mechanism of our device.